1989
DOI: 10.1056/nejm198912073212306
|View full text |Cite
|
Sign up to set email alerts
|

Intentional Injuries among Children and Adolescents in Massachusetts

Abstract: We estimated age-specific and sex-specific incidence rates of intentional injuries (assaults or suicide attempts) occurring between 1979 and 1982 in a population of 87,022 Massachusetts children and adolescents under 20 years of age in 14 communities with populations of 100,000 or less. The average annual incidence of intentional injuries treated at a hospital was estimated to be 76.2 per 10,000 person-years. Overall, 1 in 130 children was treated each year for an intentional injury. More than 85 percent of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Two studies used the same data source (Northern Manhattan Injury Surveillance System) to examine severe injuries (those resulting in hospitalization or death) but utilized two different levels of analysis: zip code of residence (23) and census tract (22). Both studies found that low SES was associated with higher injury rates among persons ages 16 and under. For the studies examining cause-specific nonfatal injuries, rates were higher in areas characterized by low SES, or inversely correlated with SES measures for head injuries (24,41,60), fire or burn injuries (32,47), pedestrian or bicyclist injuries (21,63), and intentional nonfatal injuries (28), regardless of study population and setting, source of data, covariates, or SES measure(s) used. Two of the individual-level studies examined the relationship between SES and nonfatal injuries by gender.…”
Section: Nonfatal Injuriesmentioning
confidence: 99%
“…Two studies used the same data source (Northern Manhattan Injury Surveillance System) to examine severe injuries (those resulting in hospitalization or death) but utilized two different levels of analysis: zip code of residence (23) and census tract (22). Both studies found that low SES was associated with higher injury rates among persons ages 16 and under. For the studies examining cause-specific nonfatal injuries, rates were higher in areas characterized by low SES, or inversely correlated with SES measures for head injuries (24,41,60), fire or burn injuries (32,47), pedestrian or bicyclist injuries (21,63), and intentional nonfatal injuries (28), regardless of study population and setting, source of data, covariates, or SES measure(s) used. Two of the individual-level studies examined the relationship between SES and nonfatal injuries by gender.…”
Section: Nonfatal Injuriesmentioning
confidence: 99%
“…Females were more likely to be transported for suicide and drug intoxication, whereas males were more likely to be transported for assault and alcohol. Male overrepresentation in assault situations has been previously described 14,16,17 and is not, therefore, surprising. Our nearly equal female representation in transport for drug intoxication is consistent with studies reporting that girls experiment with drugs at younger ages than boys do.…”
Section: Discussionmentioning
confidence: 53%
“…Each year in Massachusetts, 1 in 303 female adolescents received hospital care for a suicide attempt, and drug overdose was the method used most often for these attempts (Guyer et al, 1989). More than one third of ingestions by adolescents involve over the counter medications such as aspirin and one quarter involve psychotropic medications or sedatives (Guyer et al, 1989 andTrinkoff &Baker, 1986).…”
Section: Poisoningmentioning
confidence: 99%